The carbon footprint of young-beef cattle finishing systems in the Eastern Plains of the Orinoco River Basin of Colombia - Ramírez-Restrepo, Carlos A.; Vera-Infanzón, Raul R.; Rao, Idupulapati M. (Frontiers in Animal Science, 2023)
Previous research has shown increased productivity amongst sown grass pastures compared to native savanna pastures by year-round grazing for fattening of adult and young Brahman (Bos indicus)-bred cattle in the well-drained native savanna ecosystem of the Colombian Orinoquía. But there is limited information on the carbon footprint (CF) of commercial young-Brahman heifers and steers reared throughout life on well-managed Brachiaria decumbens Stapf pastures. The present study characterized growth, lifetime enteric methane (CH4) emissions, carcass carbon dioxide equivalent (CO2-eq) CH4 efficiency intensities (i.e., emissions per kg of product), and estimated the overall CF of young cattle grazing B. decumbens pastures subject to a range of daily liveweight gains (DLWGs; 0.428 – 0.516 kg) and fattening framework (405 – 574 kg). Weaning data from seven consecutive calving seasons in a commercial Brahman breeding herd continuously grazed on B. decumbens were integrated with a Microsoft Excel® dynamic greenhouse gas emission (GHGE) simulation of stockers-yearlings, and seven fattening, and processing scenarios. The model predicted that heifers subject to low and high DLWGs (0.428 vs 0.516 kg) and steers (0.516 kg) may be successfully fattened without supplementation assuming that animals had access to a well-managed grass pasture. Depending on the fattening strategy, kg CO2-eq CH4/kg edible protein values ranged from 66.843 to 87.488 ± 0.497 for heifers and from 69.689 to 91.291 ± 0.446 for steers. Assuming that forage on offer is at least 1,500-2,000 kg of dry matter/ha during the rainy season, all the simulated systems showed potential for C neutrality and net-zero C emission when considering GHGEs from the soil, pasture, and animal components vs the estimated soil C capture over seven seasons. However, under a more optimistic scenario, these beef systems could accomplish substantial net gains of soil C, over the period for which field data are available. Overall, this study projects the positive impact of the design of plausible fattening strategies on grasslands for improving cattle productivity and reducing emission intensities with concomitant increases in technical efficiency.